Are Community Preparing for Coastal Hazards? A Case Study on a Small Island in Aceh, Indonesia - Furqan Ishak Aksa; Rina Suryani Oktari; Faiz Urfan (Department of Geography Education, University of Jember, 2023)
Coastal areas are experiencing a high population density that is increasing the vulnerability of community to coastal hazards. Therefore, this study aimed to comprehensively evaluate the preparation level of community to confront coastal hazards. Disaster preparedness was recognized to play an essential role in reducing potential losses caused by flood. However, limited studies assessed community preparedness on small islands using face-to-face interviews with community. A household survey was also conducted on community living on Pusong Island. The results showed that community preparedness was still low (38.34% of 100). Even though tidal flood events were experienced, community were not forced to take preparedness actions and move from Pusong Island. The low level was due to socialization activities and community capacity building related to coastal hazards rarely performed by the government. This study also suggested the importance of increasing the preparedness on remote islands through integrated coastal area management.